Carbon-Based Nanosensor Technology - Kranz, Christine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Carbon nanomaterials have gained relevance in chem/bio sensing applications owing to their unique chemical, mechanical, electrical, and thermal characteristics. Written by leading experts in the field, this book discusses selected, state-of-the art carbon-based nanomaterials, including nanodiamonds, graphene nanodots, carbon nanopores, and nanocellulose. It presents examples of chem/bio sensing applications ranging from biomedical studies, such as DNA sequencing and neurotransmitter sensing, to heavy-metal detection in environmental monitoring scenarios, and reviews the unique properties of carbon-based nanomaterials with respect to targeted sensing applications. Further, it highlights exciting future applications. Providing comprehensive information for practitioners and scientists working in the field of carbon nanomaterial technologies and their application, it is also a valuable resource for advanced students of analytical chemistry, biochemistry, electrochemistry, materials science, and micro-/nanotechnology and -sensing.
Diamond nanowires: A recent success story for biosensing -- Boron-Doped Diamond and Graphitic Multiarrays for Neurotransmitter Sensing -- Heavy-metal sensing based on Diamond electrodes -- Diamond waveguides for analytical spectroscopy -- Diamond Nanoparticles for Drug Delivery Applications -- Graphene-Based Electrochemical Sensors -- A Survey of Graphene-Based Field Effect Transistors for Bio-Sensing -- Carbon dots for bioimaging and biosensing applications -- DNA Sequencing Using Carbon Nanopores -- Promising Sensing Platforms Based on Nanocellulose.
Keywords: Nanochemistry; Biomedical engineering; Nanoscience; Nanotechnology; Nanochemistry; Biomedical Engineering and Bioengineering; Nanophysics; Nanotechnology